Monitoring of pH, Oxidation-Reduction Potential and Dissolved Oxygen to Improve the Performance of Dimethyl Phthalate Removal From Aqueous Solutions - Ali Reza Rahmani; Mohammad Taghi Samadi; Reza Shokoohi; Hassan Zolghadr Nasab (Hamadan University of Medical Sciences, 2015)
Since the process of heterogeneous Fenton is more complex and dynamic than the common Fenton process, control and online monitoring is entirely vital for optimum operation of this system. This study was aimed to investigate the effects of pH, oxidation-reduction potential (ORP) and dissolved oxygen (DO) variations on dimethyl phthalate (DMP) removal from aqueous solutions using the heterogeneous Fenton process with nano zero-valent iron (nZVI). Parameters affecting the process like contact time (5 - 120 minutes), pH (2 - 10), H2O2 concentration (0.01 - 1 mmol/L) nZVI content (0.01 - 0.5 g/L) and initial DMP concentration (2 - 50 mg/L) were also studied. It was found that, at optimum amounts (pH = 4, H2O2 concentration = 0.1 mmol/L, nZVI = 0.05 g/L, initial DMP concentration = 2 mg/L, and contact time = 60 minutes), approximately 98% of the pollutant was removed. This process could treat DMP well from aqueous environments and can be introduced as a cheap and effective method.